The Impact of Non-Oil Exports on Balance of Payment Disequilibrium in Nigeria - Adeyemi, Paul Adeniyi; Adewumi , Aladesanmi Kayode (International Journal of Finance Research, 2022)
The over-reliance on oil export revenue with little attention to non-oil export has subjected the Nigerian economy to recurring adverse external shocks which further aggravate the problem of balance of payment deficit in Nigeria. Therefore, study set out to examine the impact of non-oil exports on balance of payment disequilibrium in Nigeria. The data used for this study is secondary in nature and it spans from 1970 to 2018. The study employed econometric tools of ARDL Cointegration analysis and ARDL Error Correction Model to explore the long run relationship and the impact of non-oil exports on balance of payment disequilibrium respectively. The result of Wald bound test revealed that there is existence of co-movement between non-oil exports and balance of payment while long run ARDL Error Correction Model results showed that non-oil export has significant negative impact on balance of payment disequilibrium. In the same vein, inflation and interest rate also have negative impact on balance of payment disequilibrium but interest rate is insignificant.  Findings from the study also exhibited positive relationship between exchange rate, trade openness and balance of payment. However, the positive impact of exchange rate on balance of payment is significant while that of trade openness is not significant. The study, thus concluded based on the findings that the non-oil export has not been contributing positively to improve the balance of payment position in Nigeria. In line with these findings, the study recommended that government should devise plans and strategies of boost the non-oil export sectors such as agricultural, manufacturing, solid minerals and service sectors in order to build virile and strong non-oil export sectors that can achieve favourable balance of payment. Moreover, the citizens of Nigeria should be motivated by one way or the others to have a taste for locally produced goods.